School-based language revitalization in practice: Implementing programs for the preservation of East Makian - Ikram Senen; Roswita M. Aboe (Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the implementation of a language revitalization program for East Makian, an endangered language, within senior high school settings. It further investigates the discrepancy between policy directives and actual classroom practices, given the language’s persistent endangered status. The primary objectives are threefold: to determine the program’s effect on students’ cultural awareness and interest; to assess its impact on the number of proficient speakers; and to identify the facilitating and hindering factors affecting program implementation. A mixed-methods explanatory sequential design was employed, involving 183 student participants and five key informants across three schools. Findings indicate that the program’s overall impact was rated as Good (34.68), characterized by a significant increase in students’ cultural awareness and interest. The program’s effectiveness was also rated as Good (34.48); however, this was structurally constrained by the absence of a formal curriculum. Supporting and impeding factors received a rating of Fairly Good (33.80), with teacher commitment identified as a key facilitator, while the lack of a standardized curriculum remained a major barrier. Notably, no statistically significant difference was observed between the group exposed to the program and the non-exposed group (t = 0.052, p = 0.958). These results suggest that while the program positively influences attitudinal outcomes, it does not lead to measurable improvements in students’ productive language skills.